2015
DOI: 10.1373/clinchem.2015.239673
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Glycosylation on Diagnostic and Prognostic Accuracy of N-Terminal Pro–B-Type Natriuretic Peptide in Acute Dyspnea: Data from the Akershus Cardiac Examination 2 Study

Abstract: BACKGROUND The N-terminal part of pro–B-type natriuretic peptide (NT-proBNP) is glycosylated, but whether glycosylation influences the diagnostic and prognostic accuracy of NT-proBNP measurements is not known. METHODS We measured NT-proBNP concentrations of 309 patients with acute dyspnea by use of standard EDTA tubes and EDTA tubes pretreated with deglycosylation enzymes. The primary cause of dyspnea was classified as heart … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 46 publications
(29 citation statements)
references
References 28 publications
0
28
0
Order By: Relevance
“…There are interindividual differences in NT-proBNP and proBNP glycosylation patterns in patients with and without heart failure and therefore current NT-proBNP immunoassays underestimate "true" NT-proBNP concentrations. Assessment of deglycosylated NT-proBNP concentrations also has been shown to improve the diagnostic and prognostic accuracy in patients with dyspnea, which suggests the antibody configurations used in NTproBNP assays could be improved if glycosylated peptides were also detected (27 ).…”
Section: Discussionmentioning
confidence: 99%
“…There are interindividual differences in NT-proBNP and proBNP glycosylation patterns in patients with and without heart failure and therefore current NT-proBNP immunoassays underestimate "true" NT-proBNP concentrations. Assessment of deglycosylated NT-proBNP concentrations also has been shown to improve the diagnostic and prognostic accuracy in patients with dyspnea, which suggests the antibody configurations used in NTproBNP assays could be improved if glycosylated peptides were also detected (27 ).…”
Section: Discussionmentioning
confidence: 99%
“…Akershus University Hospital, a Norwegian teaching hospital with a catchment area of approximately 460 000 subjects, and the details of the study has previously been reported [15].…”
Section: Akershus Cardiac Examination (Ace) 2 Studymentioning
confidence: 99%
“…We used a standardized questionnaire to collect relevant data from the patients and the physicians in the ED as previously reported [15]. Analogous to previous studies on patients with acute dyspnea [2][3][4], the ED physicians were asked to assess the probability of acute HF being the main cause of dyspnea from 0% (highly unlikely) to 100% (very likely) after their initial assessment of the patient and prior to results of NT-proBNP testing.…”
Section: Data Collectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Glycosylated proBNP 1-108 also seems to represent the major form by means of which BNP immunoreactivity is released from cardiomyocytes, both in disease states and in healthy subjects. Thus, in addition to influencing the diagnostic and prognostic accuracy of the commercially available NT-proBNP assay (ProBNP assay, Roche Diagnostics, Penzberg, Germany) [6], glycosylation of proBNP 1-108 could have implications for the clinical relevance of the results by Chang et al [2 ]as limited endogenous BNP 1-32 may actually be available in healthy subjects and in patients with cardiovascular disease. Moreover, and also important for the clinical relevance of their study, the proportion of intact BNP 1-32 in patients appears to be very low because BNP 1-32 molecules are truncated from the C-terminal end [reviewed in [5]].…”
mentioning
confidence: 99%